PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT (CRM) TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PT. NASMOCO ABADI MOTOR KARANGANYAR (Studi pada pelanggan yang menggunakan jasa bengkel PT. Nasmoco Abadi Motor Karanganyar) - Adila Yeni Rosy D.; Bulan Prabawani (Universitas Diponegoro, 2018)
The development of Indonesia’s economic is experiencing tighter competition. The occurance of car sales in Indonesia that up and down, make the entrepreneurs in the automotive has to be more creative and innovative in the face of increasingly tight market competition. This research aims to examine the influence of Customer Relationship Management (CRM) on Customer Loyalty through Customer Satisfaction to PT. Nasmoco Abadi Motor. Population in thus research is customer of PT. Nasmoco Abadi Motor Karanganyar using 100 (one hundred) garage service. Data analysis of researcher use regression test, path analysis and mediation test (sobel test) by using program of SPSS 20. The result show that Customer Relationship Management have significant relation with Customer Loyalty through Customer Satisfaction. Variable Customer Satisfaction in this research is intervening variable to Customer Loyalty. The conclusion of this research proves that with the existence of Customer Satisfaction, then the customer’s perception of Customer Loyalty will increase. Furthermore, to achieve Customer Satisfaction, CRM in PT. Nasmoco Abadi Motor Karanganyar has to be further improved so that later will make the customer become loyal.